Non-pharmacological strategies to decrease anxiety in cardiac catheterization: integrative review - Natany da Costa Ferreira; Ercília da Silva Ramalho; Juliana de Lima Lopes (Associação Brasileira de Enfermagem, 2015)
ABSTRACT Objective: to identify and review the literature on non-pharmacological strategies used for reducing anxiety in patients receiving cardiac catheterization. Method: this study was an integrative literature review. The research was conducted using the databases LILACS, SciELO, Medline (through BVS and PubMed) and Scopus. Studies were analyzed according to their objective, method, instruments used for evaluating patients' anxiety, and the results obtained. Results: the most used strategy for reducing anxiety in patients receiving cardiac catheterization was music therapy. However, no study identifying the most appropriate time for this intervention (before, during and/or after the procedure) was found. Other strategies identified in this review were educational videos, massage, and palm therapy. Conclusion: the results found suggest that anxiety can be reduced using non-pharmacological strategies.